Delayed Implant Augmentation of Breast Free Flaps - Pien, Irene J.; Anolik, Rachel; Blau, Jared; Hollenbeck, Scott T. (Journal of Reconstructive Microsurgery, 2015)
Background Two commonly used breast reconstruction techniques are (1) implant-based and (2) abdominal tissue-based procedures. When the two modalities are combined, the result is a unique construct that shares advantages and disadvantages of both approaches. Combining breast flaps and implants has been reported, yet the specific techniques associated with a reliable outcome remain unclear.Materials and Methods Between July 2010 and 2014, a review of all patients who underwent delayed implant augmentation of a breast free flap reconstruction by the senior author was performed. Data were collected on patient characteristics, implants used, timing of reconstruction, and position of implant relative to the flap.Results During the study period, 101 patients underwent breast reconstruction with 161 abdominal free flaps. Of these, 12 patients (12%) and 17 flaps (11%) had delayed implant augmentation. Of the 17 augmented flaps, 12 had expanders placed before final implant placement. Eleven implants were placed in the subflap position and 6 in the subpectoralis major position. The mean final implant size was 296.5 mL (range, 125–510 mL). At a mean follow-up of 17.1 months, there was one expander removed before complete expansion for impending extrusion and one silicone gel implant revision for malposition.Conclusion The results of delayed breast flap implant augmentation can be reliable and generate results that may not be obtainable with flaps or implants alone. Admittedly, the addition of an implant to a flap reconstruction exposes the patient to implant-related complications that would otherwise have been circumvented by a pure autologous reconstruction.
Keywords: breast; flaps; implants